Development of Poly-ε-Caprolactone Based Nanoadjuvant for Effective Vaccination Against Tuberculosis - Keshvan Prashant, Chandravilas; Bhat, Madhusudan; Shamim, Mohammed; Jalees Ahmad, Farhan; Kumar Dinda, Amit (Journal of New Developments in Chemistry, 2014)
The aim of the study was to synthesize sub-100nm poly-ε-caprolactone nanoparticles (PCL NP), load them with the mycobacterial protein, ESAT 6 and study the resulting immune responses in CD4+ and CD8+ T cells when incubated with human peripheral blood monocyte derived macrophages that had internalized the PCL NP. The synthesized PCL NP were characterized for size, shape and charge. They were found to be about 60nm in size with spherical shape. MTT assay revealed that the particles were perfectly biocompatible when tested in vitro on THP1 human monocytic cell line. The particles had a slow protein release kinetics and did not degrade appreciably even after 30 days in buffer solution. ELISA was used to quantify the cytokine response of CD4+ and CD8+ T cells when incubated with the monocyte derived macrophages as antigen presenting cells. The result of antigen presentation assay revealed that the antigen loaded PCL NP enhanced Th1 and CD8+ T cell responses significantly compared to the pure antigen. Thus we conclude that PCL NP of 60nm size can be effectively tested as a vaccine adjuvant with resulting activation of Th1/Th2 immunity as well as cytotoxic T cell response.
Keywords: Tuberculosis; ESAT 6; poly-ε-caprolactone nanoparticles; antigen cross presentation; adjuvant; macrophages.